New approaches to formation of diagnosis-related groups for payment for radiotherapy and chemoradiotherapy based on clinical guidelines with the use of standardized modules of healthcare - Yu. A. Ledovskikh; E. V. Semakova; V. V. Omelyanovskiy; A. A. Kravtsov; E. A. Prokhorovich; M. V. Avxentyeva; I. A. Zheleznyakova; A. V. Petrovskiy (Biomedical Photonics)
The article presents a methodology and results of developing diagnosis related groups (DRGs) for the cases of healthcare provided with the use of radiotherapy and chemoradiotherapy for malignant neoplasms in Russian Federation. A key element of the methodology is the standardized module of healthcare (SM) which allows calculating the tariffs for medical care in accordance with clinical guidelines. As a result of the application of the new methodology, in 2019, changes were made to the DRG model in terms of payment for radiotherapy and chemoradiotherapy. The changes included developing 10 DRGs for in-patient radiotherapy and 10 DRGs in day hospital; 7 DRGs for in-patient chemoradiotherapy and 5 DRGs in day hospital. New classification criteria have been introduced into the DRG model for attributing the case to a certain DRG, in addition to the medical service used before. The number of fractions became a new criterion for radiotherapy, the number of fractions and the international non-proprietary name of the drug were proposed for chemoradiotherapy. A wider range of DRG’s weight coefficients was calculated, which allows more differentiated reimbursement of the costs of medical care provided by medical organizations depending on the method and the regimen used.